Evaluation Method of the Fatigue Life of Power Plant Pipelines - Y. Golovina, Natalya; Y. Krivosheeva, Svetlana (International Journal of Engineering and Technology, 2018)
The method for estimating the fatigue life of power plant pipelines based on the results of one or two tests without destruction is proposed. The proposed method uses the classical model of fatigue resistance. Weller curves for power plant pipelines are determined experimentally, the experimental data are presented. Three curves are constructed for the probability of destruction of 2%, 50%, and 98%. The proposed method uses the hypothesis of linear summation of Palmgren-Miner injuries. When developing the method, much attention is paid to the ways of schematizing the actual process of loading the pipelines. Calculation of the distribution of the total number of cycles was carried out by the â€œRainflowâ€ method and the Gusev method. The application of this method with a set of design measures provides more than fivefold margin for fatigue resistance of all pipelines of the power plant. Â